ARE SHARIA FINANCING SCHEMES PROFITABLE? THE CASE OF ISLAMIC RURAL BANKS IN INDONESIA - Nur Hidayah; Nur Akhlaqul Karimah (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Some studies find that Profit and Loss Sharing/PLS (mudharabah and musyarakah) and non-PLS (murabahah) financing positively affect Islamic banks' profitability, while other studies have found a negative relationship. This study aims to analyze the effect of PLS and non-PLS financing on the performance of Islamic banks, as proxied by the profitability ratio of ROA (Return on Assets) with the Non-Performing Finance (NPF) as a moderating variable on six Islamic Rural Banks (IRBs) using panel regression and moderated regression analysis. It finds that the PLS and non-PLS financing positively and significantly influence the IRBs' profitability. NPF as a moderating variable has weakened the effect of PLS financing on the IRBs' profitability. Meanwhile, NPF strengthens the effect of non-PLS financing on the IRBs' profitability. PLS financing with NPF can reduce the IRBs' profitability, and non-PLS financing with NPF can increase the IRBs' profitability. These findings explain why murabahah is still the dominant financing in Islamic banks. Islamic banks should strive to achieve their ideal form as a profit-sharing financial intermediary to respond to the criticism that there is no substantial difference between Islamic and conventional banks as both rely on fixed returns in the financing, perceived as similar to riba, prohibited in Islam.